Sportens væsen og uvæsen - en analyse af sportens historiske regimer i lyset af doping-krisen - Loshak, Jeppe; Munk, Martin D. (Forum for Idræt, 2001)
Opgør med doping som sportens uvæsen, diskussion af en debat om dopingens legitimitet i sporten. Essence and dissence of sport – its historical regimes as revealed by the doping crisis The understanding of a given social practice as taking place in a specific field requires, according to French sociologist Pierre Bourdieu, that this practice takes place in regard to sets of specific logic – hereby giving the field a certain degree of autonomy relative to the surrounding social fabric. Sports will in this article be considered to constitute such relative autonomy, but due to its great success as organizer of human energies, sport is also in a condition of a complex relation to surrounding fields of practice. The doping problem is often seen as a result of commercial interests invading the field, and the solution to the problem is often interconnected with alien forces of authority taking command. In this crisis situation where autonomy is questioned, it becomes ever more dubious what in fact constitutes the »essence« of sport – and in public debates very dividing positions are taken. In our opinion the reason for this is that sports from the very start was a conglomerate of different historical regimes – united by history and forgetfulness. With the current crisis we can once again spot these dynamics of differentiation and association.